Causes of improper body posture in children and possibility of prevention - Dedaj Marta (College of Sports and Health, Belgrade, 2020)
The modern way of life, which is characterized by insufficient movement, most often leads to poor posture. Children and young people exercise less and less and spend more and more time in passive sitting and lying positions. Such habits take them away from their natural needs for movement (hypokinesis) and significantly reduce most of their physical and functional abilities. The question is why do so many children sit with such poor posture? Habit is one of the main reasons, but not the only factor of poor posture when sitting. The article especially discusses the environment factors that may indicate the causes of improper posture, and occur during school: several hours of sitting in school desks, a large number of classes, short breaks, dysfunctional and inadequate classroom furniture, insufficient lighting of the work surface, heavy school bags and improper way of carrying one. Due to the influence of various factors: family, preschools, schools, and others in the formation of proper posture, it is necessary to create a system of preventative measures from an early age, which includes educating children. Prevention not only affects school success but also changes the attitude towards oneself, peers, and other people, which contributes to the development of positive traits and characteristics of the person and their successful socialization.